Microvesicles: Novel Biomarkers for Neurological Disorders - Borgiani, Bruno; Colombo, Elisa; Verderio, claudia; Furlan, Roberto (Frontiers in Physiology, 2012)
Microvesicles (MVs) are released by most cell types in physiological conditions, but their number is often increased upon cellular activation or neoplastic transformation. This suggests that their detection may be helpful in pathological conditions to have information on activated cell types and, possibly, on the nature of the activation. This could be of paramount importance in districts and tissues that are not accessible to direct examination, such as the central nervous system. Increased release of MVs has been described to be associated to the acute or active phase of several neurological disorders. While the subcellular origin of MVs (exosome or ectosomes) is basically never addressed in these studies because of technical limitations, the cell of origin is always identified. Endothelium- or platelet-derived MVs, detected in plasma or serum, are linked to neurological pathologies with a vascular or ischemic pathogenic component, and may represent a very useful marker to support therapeutic choices in stroke. In neuroinflammatory disorders, such as multiple sclerosis, MVs of oligodendroglial, or microglial origin have been described in the cerebrospinal fluid and may carry, in perspective, additional information on the biological alterations in their cell of origin. Little specific evidence is available in neurodegenerative disorders and, specifically, MVs of neural origin have never been investigated in these pathologies. Few data have been reported for neuroinfection and brain trauma. In brain tumors, despite the limited number of studies performed, results are very promising and potentially close to clinical translation. We here review all currently available data on the detection of MVs in neurological diseases, limiting our search to exclusively human studies. Current literature and our own data indicate that MVs detection may represent a very promising strategy to gain pathogenic information, identify therapeutic targets, and select specific biomarkers for neurological disorders.